OPTIMALISASI KEBUTUHAN TRAKTOR UNTUK PENGOLAHAN TANAH SAWAH DI KECAMATAN WUNDULAKO KABUPATEN KOLAKA - Lukman Yunus; Marsuki Iswandi; Ibtizam Hasan (Universitas Halu Oleo, 2016)
This study was conducted from October to November 2016 at the sub district of Wundulako in Kolaka regency. It aimed to analyze the finansial feasibility of hand-traktor operation at the sub district of Wundulako in Kolaka regency and to analyze the number of optimal hand-tractor needed to cultivate farm lands at the sub district of Wundulako in Kolaka regency. The study used a simple random sampling method involving 65 out of 180 farmers who owned a hand-tractor. Data were analyzed usingthe cost ratio revenue analysis (R/C ratio) and analysis of machinery needs. Types of data used were primary and secondary data. Results of the study showed that the financial feasibility of farmers who awn a hand-tractor to rent the showed an R/C ratio of 1,,46, so renting hand-tractor in the research site was beneficial with an R/C ratio of > 1. The results of a needs analysis conducted engine then obtained optimal machine to meet the needs of tractor engines with an average of 7.74 hectares of paddy processed that as many as 13 units of the machine with the efficient level of work machine 62%, and if the level of efficiency of the engine increases to 100% then tractor optimal requirements needed 7 units with the same processing area, while the increase in the work efficiency of 200% is obtained tractor engine 4 units. Further, if all tractors work the land with a total of 503 hectares processed at the rate of efficiency of 62%, 100%, 200%, the tractor is needed to optimize the needs of the 811, 503 and 251 units.Keywords : renting of hand-tractor, needs for hand-tractor.